الاستراتيجيات الفردية لأستاذ التعليم الثانوي في بناء علاقاته مع التلاميذ - بلواد مريم; قيرواني محمد أمين (University of Eloued جامعة الوادي, 2024)
Abstract: The study aimed to explore the individual strategies of the secondary school teacher in building his relationships with students, as well as undestanding the nature of teacher-student relationships in the classroom. This is done through the utilization of a phenomenological approach, which is less commonly used compared to quantitative mathods. The study relied on in-depth interviews with 20 male and female students from three secondary schools in the municipality of Jijel. The findings revealed two types of relationships between teachers and students : good relationships and conflicting relationships. Additionally , the study identified several individual strategies employed by secondary school teachers in building their relationships with students, including teaching strategies (subject mastery, classroom management), communication and interaction strategies with students, positive treatment strategies, refraining from punishing students for wrong answers , and encouragement strategies. هدفت الدراسة إلى التعرف عن الاستراتيجيات الفردية لأستاذ التعليم الثانوي في بناء علاقاته مع التلاميذ، وكذا التعرف عن طبيعة علاقات الأستاذ مع تلاميذه في القسم وذلك بالاعتماد على المنهج الظاهرتي الذي يعتبر قليل الاستعمال مقارنة بالمناهج الكمية، حيث تم الاعتماد على تقنية المقابلة المعمقة مع التلاميذ في جمع البيانات حول موضوع الدراسة وعينة متكونة من20 تلميذا وتلميذة يزاولون دراستهم بثلاث ثانويات ببلدية جيجل، وتوصلت الدراسة إلى أن هناك نوعين من العلاقات بين الأستاذ والتلاميذ متمثلة في علاقات جيدة وعلاقات صراع، كما توصلت الدراسة إلى وجود جملة من الاستراتيجيات الفردية التي يستخدمها أساتذة التعليم الثانوي في بناء علاقاتهم مع التلاميذ وهي كالتالي: استراتيجيات التدريس(التمكن من المادة، ضبط الصف)، استراتيجية التحدث والتفاعل مع التلاميذ، استراتيجية المعاملة الحسنة، استراتيجية عدم معاقبة التلميذ عند الإجابة الخاطئة، استراتيجية التشجيع.
Keywords: استراتيجيات فردية; أستاذ التعليم الثانوي; علاقات اجتماعية; تلاميذ; صف دراسي: individual strategies; secondary school teacher; relationships; students; classroom